The impact of agricultural performance on foreign trade concentration and competitiveness: empirical evidence from Romanian agriculture - Andrei, Jean Vasile; Popescu, Gheorghe H.; Nica, Elvira; Chivu, Luminita (Journal of Business Economics and Management, 2020)
Analysing the impact of agricultural performance on foreign trade concentration and competitiveness defines an important step in identifying the opportunities, challenges and proactive measures in designing a functional and marked based agricultural model. The scope of this study is to investigate the evolution of Romania’s the foreign trade competitiveness and its concentration on main destinations during 2007–2016. In this context, in the paper are identified and investigated some of the competitiveness’ mutations arisen from the Romania’s trade flows concentration and restructuration in relation with 26 of the European Union member states. It was used a unique dataset on agro -food trade output and concentration across EU countries to construct measures of trade competitiveness. The results obtained suggest the existence of a dual relationship of the Romanian agriculture competitiveness and its dependence on the EU economic area, by the concentration of the commercial relationships.